Development of Student Worksheets Based on Calligraphy Art on the Subject of Circles - Naimah, Siti; Al Wosabi, Abdullah Ghalib H. (Interval: Indonesian Journal of Mathematical Education, 2024)
Purpose of the study: The purpose of this research is to develop a student worksheet based on the art of calligraphy on the subject of class VIII circles at State Islamic Junior High School 1 Pringsewu. This research also aims to test the validity, practicality and effectiveness of the student worksheet developed. Methodology: This research uses research and development methods (Research & Development). The research subjects were 29 class VIII students at State Islamic Junior High School 1 Pringsewu. Data will be analyzed using validation instrument data analysis techniques, student response questionnaires, and learning outcomes tests. Main Findings: The main finding of this research is the development of calligraphy-based student worksheets on the subject of class VIII circles. This student worksheets includes components such as cover, table of contents, subtitles, competency standards, basic competencies, material, discussion, conclusions and practice questions. This student worksheets has gone through a process of validation and testing in learning. Novelty/Originality of this study: Research regarding the development of student worksheets based on calligraphy art on circles revealed that the integration of art and mathematics can increase students' creativity and understanding of geometric concepts. The results of this research show that an interdisciplinary approach not only makes learning more interesting, but is also effective in strengthening students' analytical and aesthetic abilities.